1999
DOI: 10.1002/etc.5620180907
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of dimethylsilanediol by microorganisms isolated from soil

Abstract: Abstract-Previous studies have shown that polydimethylsiloxane is hydrolyzed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The aim of this study was therefore to measure biodegradability data that may be reproduced whatever the soil and comparable to the results shown in Table 2, obtained in accordance with the OECD 301B method. Results showed that biodegradation in a liquid medium was more rapid and complete than in a soil environment (Chaineau et al, 1999;Sabourin et al, 1999) and confirm the hypotheses of the better availability of the substrate in a liquid medium than in a soil environment and a better oxygenation of the liquid medium facilitating the aerobic biodegradation process. Nature and origin of inocula have also a great influence on results of biodegradation (Mezzanote et al, 2005) could be an handicap for the use of this kind of test in liquid medium with different activated sludge inocula.…”
Section: Ultimate Biodegradabilitysupporting
confidence: 77%
“…The aim of this study was therefore to measure biodegradability data that may be reproduced whatever the soil and comparable to the results shown in Table 2, obtained in accordance with the OECD 301B method. Results showed that biodegradation in a liquid medium was more rapid and complete than in a soil environment (Chaineau et al, 1999;Sabourin et al, 1999) and confirm the hypotheses of the better availability of the substrate in a liquid medium than in a soil environment and a better oxygenation of the liquid medium facilitating the aerobic biodegradation process. Nature and origin of inocula have also a great influence on results of biodegradation (Mezzanote et al, 2005) could be an handicap for the use of this kind of test in liquid medium with different activated sludge inocula.…”
Section: Ultimate Biodegradabilitysupporting
confidence: 77%
“…Methylsilanols are expected to degrade photolytically in the atmosphere and in water to silica and carbon dioxide [82][83][84]. Dimethylsilanediol has also been recently shown to biodegrade to methylsilanetriol, carbon dioxide, and silica [78,90,100].…”
Section: Environmental Degradationmentioning
confidence: 99%
“…Sabourin et al [90] added 100 ppm 14C-dimethylsilanediol to four soils. All four soils produced 14C0 2 .…”
Section: Biodegradationmentioning
confidence: 99%
See 2 more Smart Citations